2017
DOI: 10.18632/oncotarget.21660
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC inhibitors enhance neratinib activity and when combined enhance the actions of an anti-PD-1 immunomodulatory antibody in vivo

Abstract: Patients whose NSCLC tumors become afatinib resistant presently have few effective therapeutic options to extend their survival. Afatinib resistant NSCLC cells were sensitive to clinically relevant concentrations of the irreversible pan-HER inhibitor neratinib, but not by the first generation ERBB1/2/4 inhibitor lapatinib. In multiple afatinib resistant NSCLC clones, HDAC inhibitors reduced the expression of ERBB1/3/4, but activated c-SRC, which resulted in higher total levels of ERBB1/3 phosphorylation. Nerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 57 publications
(153 citation statements)
references
References 43 publications
4
149
0
Order By: Relevance
“…In GBM6, but not GBM14, the drugs combined to further activate ATM and AMPK; in several prior studies using different drug combinations we have delineated an ATM-AMPK-ULK1-ATG13 pathway that promotes autophagosome formation (Figures 2A,B) (20,21,24,31). In GBM14 cells, fingolimod as a single agent strongly activated ATM-AMPK signaling.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In GBM6, but not GBM14, the drugs combined to further activate ATM and AMPK; in several prior studies using different drug combinations we have delineated an ATM-AMPK-ULK1-ATG13 pathway that promotes autophagosome formation (Figures 2A,B) (20,21,24,31). In GBM14 cells, fingolimod as a single agent strongly activated ATM-AMPK signaling.…”
Section: Resultsmentioning
confidence: 85%
“…In many prior experimental therapeutics studies, we have performed agnostic screening analyses following exposure of cancer cells to drugs using the Hermes widefield microscope. Using fluorescence intensity imaging of individual cells, we define the changes in the expression and phosphorylation of multiple signal transduction proteins (20,21,24,31). Signaling by ERK1/2, AKT, mTOR, p70 S6K, STAT3, and STAT5 was assessed, as was signaling by ATM, the AMPK and eIF2 alpha.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has been demonstrated that programmed cell death 1 or PDā€L1 expression was increased, supporting a role for combining HDAC inhibitors with immune checkpoint inhibitors (Fig. ) . Table lists representative clinical trials of these types of drug combinations in solid tumors actively enrolling as of June 2018.…”
Section: Examples Of Recruiting Clinical Trials Using Combinations Ofmentioning
confidence: 84%